Efeitos de agentes naturais na qualidade de manteiga de garrafa - Maia, Keliane da Silva (2020)
Because it is a food rich in lipids, bottle butter can develop undesirable taste and odor, through oxidative deterioration, in addition to reducing its nutritional value, through the oxidation of polyunsaturated fatty acids. In this context, the objective was to investigate the use of natural agents in the oxidative control of bottle butter, adding value and functionality, by incorporating bioactive agents, and by differentiated sensory and nutritional changes. For this, the present study consisted of two distinct experiments, namely: Experiment I: Quality and stability of bottle butter enriched with black pepper extract. Experiment II: Oxidative stability and sensory quality of smoked bottle butter. The production of bottle butter, black pepper extract and the smoking process were carried out on a laboratory scale. In both experiments, accelerated stability tests were carried out, using the greenhouse test, at temperatures of 60 ° C and 110 ° C, simulating ambient storage and cooking, respectively.Oxidation was monitored by determining the peroxide index (PI) and thiobarbituric acid reactive substances (TBARS), in samples stored at 60 ° C and 110 ° C, and by the acidity index and trans fatty acid profile only for samples stored at 110 ° C. Microbiological safety was also evaluated by the total count of viable mesophilic aerobic microorganisms (CFU / g) and the most likely number (NMP / g) of coliforms at 35 ° C and 45 ° C. In the sensory evaluation, affective tests of acceptance and purchase intention were applied. The nutritional quality indexes (Atherogenicity and Thrombogenicity) of the butters enriched with black pepper extract and the safety of the smoked butters were determined by the presence of polycyclic aromatic hydrocarbons (HPA's), potentially carcinogenic. All samples showed good acceptance, with an acceptability index above 70% for all evaluated attributes and microbiological results within the limit established in the legislation. There was no increase in the percentage of trans fatty acids. The addition of black pepper extract reduced the Atherogenicity and Thrombogenicity indexes of bottle butter. Smoking did not produce HPA’s. The addition of black pepper extract and the smoking process improve the oxidative stability of bottle butter.